Induction of vitellogenesis by 17-hydroxyprogesterone and methyl farnesoate during post-reproductive period, in the estuarine crab Neohelice granulata - Medesani, Daniel Alberto (2015)
Adult female crabs (Neohelice granulata) were treated during the post-reproductive period with both 17-hydroxyprogesterone (17PG) and methyl farnesoate (MF). During the 4-week in vivo assay, animals were fed hormone-enriched (17PG or MF) pellets twice a week, at a dose of 2 nmol/g of body weight. Additionally, at the middle of the in vivo experiment, ovarian explants were incubated in vitro with each hormone at a concentration of 15 M for 24 h. At the end of the in vivo assay, both the gonadosomatic index and the vitellogenic protein content (Vg) of crabs treated with either 17PG or MF were significantly higher (p 0.05) than the values of the concurrent controls. In addition, the hemolymphatic vitellogenin level of both hormonally treated groups was higher. At the end of the in vitro assay, ovary explants incubated with 17PG had a significantly higher (p 0.05) protein synthesis and content of Vg proteins than controls. Ovary explants incubated with MF had similar levels to controls (p 0.05). The involvement of these hormones in the regulation of ovarian growth during the reproductive cycle of N. granulata is discussed.